Death wish [videorecording (DVD)] - Willis, Bruce, 1955-; D'Onofrio, Vincent; Shue, Elisabeth; Garfield, Brian, 1939- (20th Century Fox Home Entertainment, 2018)
When his wife and daughter are violently attacked, Dr. Paul Kersey hunts down his family's assailants to deliver justice. Fury and fate collide in this intense action-thriller.